Does Motor Symptoms Asymmetry Predict Motor Outcome of Subthalamic Deep Brain Stimulation in Parkinson's Disease Patients? - Bove, Francesco; Cavallieri, Francesco; Castrioto, Anna; Meoni, Sara; Schmitt, Emmanuelle; Bichon, Amélie; Lhommée, Eugénie; Pélissier, Pierre; Kistner, Andrea; Chevrier, Eric; Seigneuret, Eric; Chabardès, Stephan; et al. (Frontiers in Human Neuroscience, 2022)
Background: In Parkinson’s disease (PD), the side of motor symptoms onset may influence disease progression, with a faster motor symptom progression in patients with left side lateralization. Moreover, worse neuropsychological outcomes after subthalamic nucleus deep brain stimulation (STN-DBS) have been described in patients with predominantly left-sided motor symptoms. The objective of this study was to evaluate if the body side of motor symptoms onset may predict motor outcome of bilateral STN-DBS. Methods: This retrospective study included all consecutive PD patients treated with bilateral STN-DBS at Grenoble University Hospital from 1993 to 2015. Demographic, clinical and neuroimaging data were collected before (baseline condition) and one year after surgery (follow-up condition). The predictive factors of motor outcome at one-year follow-up, measured by the percentage change in the MDS-UPDRS-III score, were evaluated through univariate and multivariate linear regression analysis. Results: A total of 233 patients were included with one-year follow-up after surgery [143 males (61.40%); 121 (51.90 %) right body onset; 112 (48.10%) left body onset; mean age at surgery, 55.31 ± 8.44 years; mean disease duration, 11.61 ± 3.87]. Multivariate linear regression analysis showed that the left side of motor symptoms onset did not predict motor outcome (β = 0.093, 95% CI=-1.967 to 11.497, p = 0.164). Conclusions: In this retrospective study, the body side of motor symptoms onset did not significantly influence the one-year motor outcome in a large cohort of PD patients treated with bilateral STN-DBS.